ANALISIS HOME INDUSTRI KERUPUK OPAK DI DESA JAYA BAKTI KECAMATAN MADANG SUKU I KABUPATEN OKU TIMUR - Parmaji (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2015)
The purpose of this research is to: (1) to know the technique of making opak crackers in Jaya Village Bakti Madang Suku I District of East OKU Regency, (2) Knowing the income and breakeven from opak cracker home industry in Jaya Bakti Village Madang Suku I District OKU East, (3) Knowing the added value of opak cracker home industry in Jaya Bakti Village, Madang Suku I District, OKU Timur Regency, (4) Find out if home industry of opak crackers in Jaya Bakti Village, Madang Suku I District OKU Timur is beneficial and feasible to be developed . This research was conducted in April to June 2014 at opak cracker home industry conducted by Ibu Suratmi in Jaya Bakti Village Madang Suku I District of East OKU Regency. Determining the location of the research is done purposively with the consideration that there are still not many who do opak cracker home industry, whereas raw materials are widely available. This research found that the technique of making opak crackers is easy enough that by cassava grated, seasoned (garlic, coriander and salt), then printed and steamed for ± 2 minutes for once steaming opak crackers, then dried for ± 2 days, after Crude cracker crackers are packed and then marketed. So, the process of making opak crackers takes ± 5 days. Receipt from home opal cracker manufacture industry is Rp 735.000, - / PP, with production cost Rp 501.362, - / PP, with fixed cost of Rp. 69.444, - / PP and variable cost of 428.000, - / PP then the revenue is obtained Rp 233.638 .- / PP or Rp 1.401.828 .- / Month. Value added on opak cracker manufacture amounted to Rp. 333,638, - / PP obtained from the proceeds minus intermediate expenses. The intermediate cost is obtained from the total production cost of Rp. 501,362, - / PP minus family labor cost of Rp. 100.000, - / PP so the total cost between Rp. 401.362, - / PP and profit rate based on the receipt of the value of more than 1 is R / C Ratio of 1.47 which means that opa cracker home industry is profitable. While based on the rate of profit from income is more than the prevailing bank interest rate is B / C Ratio of 0.47 which means home industry of non-feasible opak crackers. BEP production value of Rp. 53,27, - / kg / PP, BEP value of acceptance of Rp. 559.361, - / PP, and the value of BEP price of Rp. Rp. 4.386, - / kg / PP, so that this business can be considered functionally feasible. In addition, the total assets invested for home industry for a year or ROI value generate a profit of 0.38%, which means for home industry opak cracker manufacture for one year to produce profit / profit of 0.38%.